Preface - Herawan, Tutut (Journal of Information Systems Research and Practice, 2024)
The Volume 6 Issue 2 of JISRP has been available online since 14th May 2024 for the regular issue of June 2024. The issue has been available online for accepted papers (uncorrected proofs).